1999
DOI: 10.1073/pnas.96.12.6942
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene mutations are not required for early dissemination of cancer cells

Abstract: The p53 protein is involved in several central cellular processes, including gene transcription, DNA repair, cell cycling, genomic stability, chromosomal segregation, senescence, and apoptosis. Blood-borne dissemination of tumor cells is a major risk factor for metastatic relapse and cancer-related mortality in patients with operable solid tumors. With the recent development of sensitive immunocytochemical and molecular methods, individual disseminated tumor cells, undetectable by conventional tumor staging pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 38 publications
3
19
0
2
Order By: Relevance
“…Although knockout mice that are heterozygous for the p53 tumor suppressor gene are more susceptible to radiation-induced tumors, evidence suggests that LOH at this locus may not be the initiating event (Bouffler et al, 1995). In this context, it is notable that the expression of p53 mutations also appears to occur late in the process of radiation-induced malignant transformation, during the growth of the visible-transformed foci, an observation that is consistent with the findings in some human tumors (Offner et al, 1999).…”
Section: Initiating Event In Radiation Carcinogenesissupporting
confidence: 74%
“…Although knockout mice that are heterozygous for the p53 tumor suppressor gene are more susceptible to radiation-induced tumors, evidence suggests that LOH at this locus may not be the initiating event (Bouffler et al, 1995). In this context, it is notable that the expression of p53 mutations also appears to occur late in the process of radiation-induced malignant transformation, during the growth of the visible-transformed foci, an observation that is consistent with the findings in some human tumors (Offner et al, 1999).…”
Section: Initiating Event In Radiation Carcinogenesissupporting
confidence: 74%
“…Using our method, we identified MRCC with p53 LOH in only 16% of all informative cases (n = 245/353) favouring the hypothesis of major genomic differences between the primary tumour and MRCC. This fact is further substantiated by data published from Offner et al (1999) for p53 overexpression. Whereas Carter et al (1994) found LOH of D11S528 in 39% of primary tumour samples investigated, MRCC showed LOH in nearly 20% of all informative cases (n = 205/353).…”
Section: Figuresupporting
confidence: 57%
“…On the other hand, molecular detection and characterization of purified MRCC from patients has to reflect the polyclonality of malignant disorders (Aubele et al, 1999). Furthermore, GI in metastases and MRCC are quite different from alterations found in the primary tumour (Hampl et al, 1999;Offner et al, 1999). Therefore, single parameter analyses as performed by many scientific groups, does not describe the complexity of this disease.…”
Section: Figurementioning
confidence: 99%
“…Our present results indicate that cytokeratin-positive micrometastatic tumor cells represent a selected population of cancer cells; these cells, however, still express a considerable degree of heterogeneity [47,[56][57][58]. With the development of new techniques like single-cell PCR [59,60] and the in vitro expansion of micrometastatic cells [61,62], it may be possible to determine the characteristic genotypic features of those cells.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal residual disease offers the advantage of a small burden of dispersed tumor cells which are more accessible to intravenously applied drugs than gross metastases. In view of the dormant nature of micrometastatic cells in bone marrow [47,58], therapies that are also directed against quiescent cells, such as antibody-based immunotherapy, might be complementary to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%